Classification of Slope for Coffee Plantation in Ngajum District, Indonesia - Noraini, Alifah; Tjahjadi, Martinus Edwin; Jasmani, Jasmani (P3KM Politeknik Pertanian Negeri Samarinda, 2024)
Slope classification activity aims to provide information to coffee farmers about the slope, especially in Ngajum District, Malang Regency. Ngajum is one of the sub-districts located on the slopes of Mount Kawi. The people of Ngajum generally work as cattle and goat breeders as well as coffee plantations. Information on the slope (altitude) affects the classification of the quality of the coffee produced. In addition, the varieties of coffee planted also depend on the slope of the mountain slopes. Making a slope map utilizes satellite imagery which has altitude information, namely in the form of Digital Elevation Model (DEM) satellite imagery. Administrative boundary data are used according to the sub-district so that the slope classification can be focused. The method used in this activity is the analysis of spatial data from the results of slope classification. Slope class is divided into 7 (seven) slope classes, i.e. flat, wavy, wavy-bumpy, bumpy-hilly, hilly-mountainous, steep mountain, and mountainous. The results of slope classification show that 2377.171 Ha or 35.971% of the Ngajum area is undulating class. The slope of the wavy slope is a suitable class for coffee cultivation but must be accompanied by the suitability of other parameters so that the productivity of coffee plants increases. The drawback of the results of this activity is that it has not been able to determine which varieties of coffee plants are suitable for planting with the slope of the area, so further research is needed.